Report of the sixth meeting of the European Consortium ‘Care for CMMRD’ (C4CMMRD), Paris, France, November 16th 2022 - Guerrini-Rousseau, Léa; Gallon, Richard; Pineda, Marta; Brugières, Laurence; Baert-Desurmont, Stéphanie; Corsini, Carole; Dangouloff-Ros, Volodia; Gorris, Mark A. J.; Haberler, Christine; Hoarau, Pauline; Jongmans, Marjolijn C.; Kloor, Matthias; et al. (Familial cancer, 2024)
Biallelic germline pathogenic variants in one of the four mismatch repair genes (MSH2, MSH6, MLH1 and PMS2) cause a very rare, highly penetrant, childhood-onset cancer syndrome, called constitutional mismatch repair deficiency (CMMRD). The European consortium “Care for CMMRD” (C4CMMRD) was founded in Paris in 2013 to facilitate international collaboration and improve our knowledge of this rare cancer predisposition syndrome. Following initial publications on diagnostic criteria and surveillance guidelines for CMMRD, several partners collaborating within the C4CMMRD consortium have worked on and published numerous CMMRD-related clinical and biological projects. Since its formation, the C4CMMRD consortium held meetings every 1-2 years (except in 2020 and 2021 due to the Covid 19 pandemic). The sixth C4CMMRD meeting was held in Paris in November 2022, and brought together 42 participants from nine countries involved in various fields of CMMRD healthcare. The aim was to update members on the latest results and developments from ongoing research, and to discuss and initiate new study proposals. As previously done for the fifth meeting of the C4CMMRD group, this report summarizes data presented at this meeting.
Im Titel ist "4" tiefgestellt
Gesehen am 07.04.2025